Adsorption of Phenol and Iron In Wastewater Using a Mixture of Active Carbon and Zeolite Modified with Chitosan - Ratnawati Ratnawati; Rian Hidayat; M. Cece Ariwirdana; Kudrat Sunandar; Wahyudin Wahyudin (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2022)
Phenol (C6H5OH) and iron (Fe2+) contained in electroplating industrial wastewater are toxic even at small concentrations. One of the effective methods to remove these compounds is adsorption because the method is easy and simple. Activated carbon and zeolite are types of adsorbents that are often used in wastewater treatment, but both types of adsorbents are not selective in certain chemicals. In this study, modification of zeolite and activated carbon with chitosan was carried out to adsorb waste containing phenol and Fe2+. The variations used were pH (7 and 9) and the adsorbent composition to study its effect on the adsorption of phenol in the presence of Fe2+. Adsorption was carried out in a bed with circulating waste for 2 hours. Feed at pH 9 with adsorbent mixed of zeolite-chitosan composite (Z-Ch) and activated carbon-chitosan composite (AC-Ch) in a ratio of 1:1 gave the optimal results. Under these conditions, 94% and 97% of phenol and Fe2+ were adsorbed, respectively.